Correlation of maternal serum high-sensitive C-reactive protein levels with biochemical and clinical parameters in preeclampsia - Kumru, S; Godekmerdan, A; Kutlu, S; Ozcan, Z (Elsevier, 2006)
Objective: To investigate the relationship between serum high sensitive C-reactive protein (hsCRP) levels and biochemical and clinical parameters in preeclampsia (PE). Study design: This cross-sectional study included 20 women with PE and 20 healthy pregnant women. They were recruited in the third trimester of pregnancy at the Firat University, Firat Medical Center, Department of Obstetric and Gynaecology in Elazig province. The standard biochemical and hematological parameters were measured by an advanced auto analyzer. Venous blood samples were collected at admission to the hospital at least 6 It before delivery for measurement of hsCRP by a high sensitive immunonephelometric method. Results: Hemoglobin, serum hsCRP, creatinine, aspartat and alanine transaminase, lactate dehydrogenase, blood urea nitrogen and urine protein excretion were higher, and serum calcium levels were lower in patients with PE compared to control group values. In the preeclampsia group, correlation analysis tests showed a strong positive correlation between serum hsCRP levels and diastolic blood pressures (r = 0.9, p = 0.05, n = 20) and urinary protein excretion (r = 0.8, p = 0.05, n = 20), and a negative correlation between serum hsCRP and weight (r = -0.6, p = 0.02, n = 20) and length (r = -0.5, p = 0.05, n = 20) of the newborns. Serum hsCRP levels were also negatively correlated with weights (r = 0.5, p = 0.02, n = 20) and lengths (r = 0.5, p = 0.05, n = 20) of the newborns in the control group. Conclusions: Serum hsCRP levels increase in women with PE. Elevated serum levels of hsCRP in preeclamptic women are correlated with clinical and biochemical parameters of PE. Determination of serum hsCRP levels may be used as a marker for the severity of PE. (c) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: preeclampsia; eclampsia; HELLP syndrome; hsCRP